Manajemen Pembenihan Ikan Kerapu Bebek (Chromileptes Altivelis) Untuk Menghasilkan Benih Yang Optimal - Andri Iskandar; M. Arif Mulya; Ahmad Tsaqifur Rifqi; Dwi Handoko Putro; Arif Rahman Rifaie (Barakuda'45, 2022)
Humpback grouper Chromileptes altivelis is a marine fish that lives in tropical waters, especially in Indonesia. This fish has a high economic value and is the most expensive type of grouper in Indonesia. It can be used as ornamental fish or raised for consumption. Hatchery activities were started from brood rearing to produce productive broodstock, proper broodstock selection, multivitamin administration, and good environmental management. Humpback grouper was spawned en masse with a male to female ratio of 1:2. Fecundity of 1 female humpback grouper >300,000 eggs with a rematuration period of 20-30 days. Spawning using natural techniques accompanied by environmental manipulation, fish spawn for seven days during the dark moon. The number of eggs obtained was 560,000-2,000,000 eggs, with fertilization rate was 30-60%, and the hatching rate was 65-88%. The eggs that hatch into larvae were stocked with a density of 15-25 L-1. The larvae were transferred to a seed container at a size of 2-3 cm with a maintenance period of 40-45 days. Feeding at satiation using pellets measuring 1.1-2.0 mm with a protein content of 52-54% and 9-12% fat. Seeds were harvested at the age of 60 days when they reached a size of 5-6 cm, the survival rate was 3-5%.